The Influence of Leadership Style, Motivation and Work Environment on Employee Performance Through Job Satisfaction - Sonawi Sonawi; Wahyudi Wahyudi; Ruknan Ruknan (Indonesian Development of Economics and Administration Journal, 2025)
This study aims to analyze the influence of leadership style, motivation, and work environment on employee performance with job satisfaction as a mediating variable at Teraskota Mall Management, South Tangerang City. The research problem was motivated by fluctuating employee performance achievements ranging from 62% to 74% that had not met the 100% company targets during 2020-2024 period. Methodology/approach – The study employed a quantitative approach with survey method. The population consisted of all 129 employees of Teraskota Mall Management, using census sampling method. Data were collected through questionnaires using Likert scale and analyzed using Partial Least Square (SmartPLS 4) to test ten research hypotheses. Findings – Results revealed that leadership style, motivation, and work environment had positive and significant effects on job satisfaction. Leadership style and motivation significantly influenced employee performance, while work environment did not directly affect performance. Job satisfaction significantly influenced employee performance. Mediation analysis showed that job satisfaction successfully mediated the effects of motivation and work environment on performance, but not for leadership style.